Analisis Runutan Nukleotida Gen Protein Selubung Dua Strain Peanut Stripe Virus - Hasriadi Mat Akin (Universitas Gadjah Mada, 2000)
Nucleotide sequence analysis of coat protein gene from two biological strains of peanut stripe virus (PStV), severe blotch (PStV-Isb) and stripe (PStV-Is), has been done to study molecular variation of these strains. Comparison of predicted amino acid sequence of PStV coat protein with other members of bean common mosaic virus (BCMV) subgroup was also carried out to study the taxonomic: relationship between PStV and BCMV subgroup. The CP gene from these strains contained 861 nucleotides (nts) and encoded 287 amino acids. There were seven nucleotides of the CP gene and one nucleotide of NIb cistron that were different between PStV-Is and PStV-Isb. However, only one nucleotide at position 9309 of the CP gene caused differential amino acid residue at position 49 of the coat protein, methionine (M) for PStV-Isb and isoleucine (I) for PStV-Is. Comparison of the ammo acid sequences revealed a sequence similarity of 89,9-90,9% of PStV and other BCMV subgroup. These results provide evidence that PStV and other BCMV subgroup are in the same virus with different strain.